2013
DOI: 10.1371/journal.pone.0063599
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Gonadal Aromatase (cyp19a1) in Temperature-Dependent Sex Determination of Red-Eared Slider Turtles

Abstract: In the red-eared slider turtle (Trachemys scripta), a species with temperature-dependent sex determination (TSD), the expression of the aromatase gene during gonad development is strictly limited to the female-producing temperature. The underlying mechanism remains unknown. In this study, we identified the upstream 5′-flanking region of the aromatase gene, gonad-specific promoter, and the temperature-dependent DNA methylation signatures during gonad development in the red-eared slider turtle. The 5′-flanking r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 66 publications
(68 reference statements)
5
101
2
1
Order By: Relevance
“…This initial portion of the TSP occurring before the onset of sexually dimorphic differentiation is more consistent with TSPs reported in turtle species, where thermosensitivity is observed prior to the sexually dimorphic gonadal differentiation and continues until shortly after this dimorphism is established (Bull & Vogt 1981, Pieau & Dorizzi 1981, Wibbels et al 1991. Recent reports in turtles and alligators have demonstrated a role for epigenetic patterning in coordinating sexually dimorphic gene expression (Matsumoto et al 2013. The finding that the effects on sex ratios resulting from pulses of FPT, occurring prior to the onset of histological and transcriptional sexual dimorphism, were not reversed by subsequent incubations provides insights into the stability of the mechanisms underlying this early thermosensitivity.…”
Section: Discussionsupporting
confidence: 87%
“…This initial portion of the TSP occurring before the onset of sexually dimorphic differentiation is more consistent with TSPs reported in turtle species, where thermosensitivity is observed prior to the sexually dimorphic gonadal differentiation and continues until shortly after this dimorphism is established (Bull & Vogt 1981, Pieau & Dorizzi 1981, Wibbels et al 1991. Recent reports in turtles and alligators have demonstrated a role for epigenetic patterning in coordinating sexually dimorphic gene expression (Matsumoto et al 2013. The finding that the effects on sex ratios resulting from pulses of FPT, occurring prior to the onset of histological and transcriptional sexual dimorphism, were not reversed by subsequent incubations provides insights into the stability of the mechanisms underlying this early thermosensitivity.…”
Section: Discussionsupporting
confidence: 87%
“…In this example, DNA methylation of the gonadal aromatase (Cyp19a1) promoter was associated with temperature-induced sex ratio shifts (NavarroMartín et al, 2011). In T. scripta, the DNA methylation level of the gonadal Cyp19a1 promoter was higher at MPT than FPT by stage 19 onwards, and was reduced in response to temperature shifts from MPT to FPT (Matsumoto et al, 2013a). Similarly, differential incubation temperatures resulted in dimorphic DNA methylation patterning of the Cyp19a1 and Sox9 promoters in gonads of American alligator embryos (Parrott et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms, including DNA methylation, histone modification and non-coding RNAs, can integrate environmental information with the regulation of gene expression, and have been emerging as a promising regulatory mechanism for TSD (Matsumoto et al, 2013a;Navarro-Martín et al, 2011;Parrott et al, 2014;Piferrer, 2013;Venegas et al, 2016). The first example of an epigenetic mechanism mediating temperature effects on sexual development in a vertebrate came from a study on the European sea bass, a fish with a polygenic system of sex determination where temperature and genetics contribute equally to sexual fate.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the CYP19A1 promoter, the SOX9 promoter is hypermethylated in the gonads of embryos incubated at FPT relative to MPT [Parrott et al, 2014]. Recent studies in the red-eared slider have also shown that the putative CYP19A1 promoter is methylated at elevated levels in those embryos incubated at MPT relative to those at FPT [Matsumoto et al, 2013]. This reported dimorphic methylation originates during the TSP, suggesting that it plays an integral role in sex determination.…”
Section: Mechanisms Of Temperature-dependent Sex Determination In Repmentioning
confidence: 93%